Neo-antigen specific cancer vaccines for acute lymphoblastic leukemia—challenges, opportunities, and future directions - Victoria Bloch Blytt Sandstad; Signe Modvig; Morten Orebo Holmström (Cancer Immunology, Immunotherapy)
Abstract Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy, with standard treatment consisting of intensive chemotherapy and corticosteroids. While curative in most cases, this regimen leads to significant toxicity and long-term sequelae. Recent advancements in cancer immunotherapy, including chimeric antigen receptor T cells and bispecific T cell engagers, have improved outcomes, yet are limited by toxicity and immune escape by target downregulation. Thus, novel less toxic treatment modalities are highly warranted. The tumor mutational burden in ALL is low, which results in a low number of potentially immunogenic neo-antigens that could be used as targets for neo-epitope-specific therapeutic cancer vaccines. However, recent findings in solid cancer demonstrate that it is not the quantity but the quality of neo-antigens in the tumor that determine the tumor-specific immune response. Furthermore, novel sequencing techniques such as long-read sequencing and optical genome mapping can identify unknown genetic aberrations that may be targeted by neo-antigen vaccines. In ALL, both the ETV6-RUNX1 and BCR-ABL1 fusion genes, and the RAS-isoform mutations are frequent, and these genomic alterations generate immunogenic neo-epitopes. Additionally, therapeutic cancer vaccinations are well suited for ALL as the tumor burden is extremely low at time of a potential post-induction vaccination therapy, and patients are relatively young and are therefore less affected by immunosenescence. Thus, we envisage that neo-antigen specific therapeutic cancer vaccines could pose an important modality in future treatment algorithms for ALL.